Rethinking the Unity and Reception of Luke and Acts. Edited by Andrew F. Gregory and C. Kavin Rowe - Hays, Christopher M. (The journal of theological studies, 2011)
Rethinking the Unity and Reception of Luke and Acts opens with a confession from no lesser light than François Bovon. With a bold stroke, Bovon ushers in a volume assaulting the critical consensus to which he himself is party; he acknowledges that he had not previously given sufficient credence to the minority view that Luke and Acts are not two parts of a single work generally referred to as ‘Luke–Acts’. Without abandoning his previous position, Bovon ushers readers into the debate on whether or not Luke and Acts should be regarded as interlocking chapters of a single story., Rethinking the Unity and Reception of Luke and Acts (henceforth, Rethinking) proceeds in three parts, the first of which is a detailed Forschungsgeschichte.